Feasibility and implementation of ex vivo fluorescence confocal microscopy for diagnosis of oral leukoplakia: preliminary study - Shavlokhova, Veronika; Flechtenmacher, Christa; Sandhu, Sameena; Vollmer, Michael; Vollmer, Andreas; Pilz, Maximilian; Hoffmann, Jürgen; Ristow, Oliver; Engel, Michael; Freudlsperger, Christian (Diagnostics, 2021)
Background: Oral leukoplakia is a potentially malignant lesion with a clinical impression similar to different benign and malignant lesions. Ex vivo fluorescence confocal microscopy is a developing approach for a rapid “chairside” detection of oral lesions with a cellular-level resolution. A possible application of interest is a quick differentiation of benign oral pathology from normal or cancerous tissue. The aim of this study was to analyze the sensitivity and specificity of ex vivo fluorescence confocal microscopy (FCM) for detecting oral leukoplakia and to compare confocal images with gold-standard histopathology. Methods: Imaging of 106 submosaics of 27 oral lesions was performed using an ex vivo fluorescence confocal microscope immediately after excision. Every confocal image was qualitatively assessed for presence or absence of leukoplakia by an expert reader of confocal images. The results were compared to conventional histopathology with H&E staining. Results: Leukoplakia was detected with an overall sensitivity of 96.3%, specificity of 92.3%, positive predictive value of 93%, and negative predictive value of 96%. Conclusion: The results demonstrate the potential of ex vivo confocal microscopy in fresh tissue for rapid real-time assessment of oral pathologies.
Gesehen am 09.07.2021